Immune parameters of patients in different periods of coronavirus infection - A. A. Ploskireva; Z. F. Kharaeva; A. R. Marzhokhova; Zh. B. Ponezheva; M. Yu. Marzhokhova (Лечащий Врач)
Background. COVID-19 is a viral infectious disease that has infected more than 40 million people. The relevance of studying various mechanisms of immunological protection in the acute and post-acute periods of this disease is beyond doubt.Objective. The aim of the work was to assess the state of the indicators of blood cells, phagocytic activity and ATP in white blood cells, depending on the period of coronavirus infection caused by the SARS-CoV-19 virus.Materials and methods. There were 70 patients (41 women and 29 men) in the acute period of covid and 54 patients (38 women and 26 men) in the post-acute period aged from 18 to 68 years. The patients were examined in the acute period of the disease (upon admission to the hospital), in the period of early convalescence (before discharge from the hospital), in the post-acute period 30-35 days after discharge from the hospital and 90-95 days after discharge. In all patients, the number of leukocytes, lymphocytes and neutrophils in peripheral blood was calculated in absolute numbers and percentages of t, the concentration of ATP and phagocytic parameters were estimated.Results. Changes in the composition of the leukocyte formula in the dynamics of the infectious viral process were detected depending on the severity of COVID-19. The long-lasting proinflammatory nature of pathological changes in the body against and after COVID-19 leads to depletion of the energy potential of innate immunity cells, what follows from the concentration of ATP and significantly reduced phagocytic parameters in acute and post-acute periods in patients regardless of the severity of the coronavirus infection. In the long-term period (90-95 days after discharge), normalization of some phagocytic parameters was not detected in the group of patients who had a severe form of COVID-19, which may be the cause of various bacterial and fungal pathologies and which should be taken into account in the selection of methods for preventing the development of complications.